SAT0136 Rheumatoid Arthritis, Biologic Therapies and Respiratory Infection Risk Audit. (9th June 2015) - Nicholson, T.W.; Low, R.; David, J.
Abstract : Background: Rheumatoid arthritis (RA) is associated with an increased risk of infection. Chest disease is the second commonest cause of death. Biologic therapies are used in RA to modify disease progression. Studies have demonstrated that influenza vaccination rates exceed pneumococcal vaccination rates in patients with RA [1] . Objectives: To analyse patients with RA from the Oxford Rheumatology service against the following BSR and BHPR guidelines [2, 3] : – All patients on biologic treatment should receive influenza and pneumococcal vaccinations (unless contraindicated). – All patients need to be aware of the increased risk of infection if on an anti-TNF agent. Methods: The audit comprised 2 parts: "A" and "B". "A" was a prospective audit of 50 patients with seropositive RA on biologic therapy over 18 years of age. Patients in the rheumatology day unit, ward and biologics clinic completed a purposely-designed questionnaire in Autumn 2014. "B" was a prospective audit of 20 patients with RA on biologic therapy over 18 years of age. This was undertaken in January 2015 after the importance of vaccination had been highlighted to the local multi-disciplinary team. Results: "A": 62% of patients had been vaccinated within the last year against influenza. 36% had been vaccinated against pneumococcus. 57% on anti-TNF were aware of the increased risk of chest infection. These results were presented to the rheumatology multi-disciplinary team thereby increasing local awareness. Audit "B" was completed in January 2015. This showed a non-staistically significant improvement in influenza vaccination rates compared to "A" (80% Vs 62%; X 2 =2.12, p>0.05). There was no difference in vaccination rates against pneumococcus (30% Vs 36%; X 2 =0.58, p>0.05). 4 of the 5 patients who gave a reason for not being vaccinated against pneumococcus cited a lack of awareness. 95% were aware that they were eligible for influenza vaccination versus 50% for pneumococcus. 78% reported being made aware by their GP versus 17% by the rheumatology department. 2 out of 3 people on an anti-TNF agent were aware of the increased risk of chest infection. Conclusions: There is pulmonary morbidity attached to the use of biologic agents when treating RA and some of this is avoidable if patients are appropriately vaccinated. The rates of influenza and pneumococcal vaccination in our department are consistent with those reported elsewhere in the literature and do not meet the 100% target as set out in national guidelines. Highlighting the issue within our department has been associated with an increase in influenza vaccination rate although there is no evidence that this is causal. There was no effect upon pneumococcal vaccination rates. The results suggest that unawareness of the vaccination was the main reason for low uptake and that the majority of patients who were aware found out from their GP rather than the rheumatology department. To take advantage of this a letter is now sent to the General Practice whenever a patient is commenced on a biologic agent highlighting the need for up to date vaccinations. We plan to repeat the audit to determine whether this has an effect. References: Feuchtenberger M. 2012 Vaccination survey in patients with rheumatoid arthritis: a cross-sectional study Rheumatology International 32(6) BSR and BHPR rheumatoid arthritis guidelines on safety of anti-TNF therapies (2010) BSR and BHPR guidelines on the use of rituximab in rheumatoid arthritis (2011) Disclosure of Interest: None declared